Association between inflammatory cytokines in the aqueous humor and hyperreflective foci on optical coherence tomography in patients with neovascular age-related macular degeneration and polypoidal choroidal vasculopathy - Mao, Jianbo; Chen, Nuo; Zhang, Shian; Fang, Yuyan; Zheng, Zicheng; Wu, Sulan; Ye, Xin; Chen, Yijing; Chen, Yiqi; Shen, Lijun (Frontiers in Medicine, 2022)
Purpose To investigate the associations between cytokine levels in the aqueous humor (AH) and hyperreflective foci (HF) on spectral-domain optical coherence tomography (SD-OCT) in neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV). Methods The prospective study included 63 eyes with nAMD, 44 with PCV, and 43 with cataracts (Controls). AH samples were obtained before anti-vascular endothelial growth factor (VEGF) therapy or cataract surgery. Cytokines interleukin 6 (IL-6), IL-8, IL-10, interferon-inducible protein 10 (IP-10), monocyte chemotactic protein 1 (MCP-1), and VEGF were measured by multiplex bead assay. Best-corrected visual acuity (BCVA), central macular thickness (CMT), and the number of HF were evaluated at baseline and 1 month after anti-VEGF treatment. Results No significances difference in IL-6 and IL-8 levels were noted among the three groups (P = 0.370 and P = 0.067). VEGF, IP-10, and IL-10 levels were significantly higher in nAMD and PCV groups than in Controls (all P < 0.05). In nAMD, HF was positively correlated with VEGF (rs = 0.300, P = 0.025) and in eyes with HF group, VEGF and IL-10 were significantly higher than those without HF (P = 0.008 and P = 0.022). In PCV, no correlation was observed between HF and cytokines (all P > 0.05). After anti-VEGF treatment, patients with HF in nAMD and PCV were predisposed to worse visual outcomes (P = 0.022 and P = 0.015) and a significantly greater reduction in CMT (P = 0.001 and P = 0.057). And nAMD patients with HF were more sensitive to anti-VEGF treatment than those without HF (P = 0.029). Conclusions In the nAMD group, HF was positively correlated with VEGF. Patients in nAMD with HF had elevated levels of VEGF and IL-10 and responded favorably to anti-VEGF. HF might serve as an inflammatory biomarker and a predictive factor for therapeutic efficacy in patients with nAMD.